Unintended Consequences of Family Planning Policies on the Breastfeeding Gap between Sons and Daughters - Minhee Chae; Yong Cai; Jun Hyung Kim; William Lavely (Institute of Labor Economics (IZA), 2023)
We examine the effect of a Chinese family planning policy (FPP) known as "Later, Longer, and Fewer" on the gender gap in breastfeeding. We find that FPP increased the daughter-son breastfeeding gap in favor of sons in rural areas. Mean intensity of the FPP predicts the gender gap to be 35% greater than the gap without FPP. The effects are explained by the skewed gender composition of last-born children produced by sex-selective stopping behavior. The findings indicate a way in which FPP, in the context of son preference, widens gender gap in child development.
Keywords: J1; J13; J16; J18; 330; breastfeeding; "Later-Longer-and-Fewer" campaign; son preference; family planning